Recent Trends in World and U.S. Mango Production, Trade, and Consumption - Edward A. Evans (EDIS, 2008)
FE718, a 7-page article by Edward A. Evans, summarizes some of the recent trends in world and U.S. mango production, trade, and consumption. Includes references. Published by the UF Department of Food and Resource Economics, August 2008.